PENGARUH REPETITIVE TRANSCRANIAL MAGNETIC STIMULATION (r-TMS) TERHADAP INTENSITAS NYERI PENDERITA CENTRAL POST-STROKE PAIN (CPSP) - Dody Perdana Goenadhi; Jumraini Tammasse; David Gunawan (PERDOSNI, 2018)
EFFECTS OF REPETITIVE TRANSCRANIAL MAGNETIC STIMULATION (r-TMS) TOWARDS PAIN INTENSITY IN PATIENTS WITH CENTRAL POST-STROKE PAIN (CPSP)ABSTRACTIntroduction: About 2,7% patients have experienced central post-stroke pain (CPSP) after stroke attack. Repetitive transcranial magnetic stimulation (r-TMS) is a nonpharmacological method to overcome CPSP.Aims: To determine the effectiveness of r-TMS to reduce pain intensity in patients with CPSP.Methods: Randomized-controlled trial in Wahidin Sudirohusodo hospital and Inggit clinic from December 2017 until May 2018. Subjects were divided to 2 groups; control, who received standard therapy for CPSP, and treatment, who received standard therapy for CPSP and r-TMS. Repetitive transcranial magnetic stimulation was done using 2000 pulse and 10Hz frequency. Pain intensity was measured with Numerical Pain Rating Scale (NPRS) at baseline, after r-TMS until day 10. Data analysis was done by Mann-Whitney test.Results: As much as 30 subjects were divided into 2 groups (15 control and 15 treatment). The difference in NPRS score after 10 days of treatment was statistically higher in the treatment group compared to the control (6,67 vs 4,67, p=0,002).Discussion: There was a significant reduction in pain intensity in the group given r-TMS for 10 cycles.Keywords: Central pain, NPRS, r-TMS, strokeABSTRAKPendahuluan: Sebanyak 2,7% pasien mengalami central post-stroke pain (CPSP) setelah serangan. Efektivitas repetitive transcranial magnetic stimulation (r-TMS) merupakan salah satu metoda nonfarmakologis untuk mengatasi CPSP.Tujun: Mengetahui efektivitas repetitive transcranial magnetic stimulation (r-TMS) terhadap penurunan intensitas nyeri pada penderita CPSP.Metode: Uji klinis terandomisasi di RSUP Dr. Wahidin Sudirohusodo dan Klinik Inggit dari Desember 2017 hingga Mei 2018. Subjek dibagi menjadi 2 kelompok, kelompok kontrol yang mendapat terapi standar dan kelompok perlakuan yang ditambahkan r-TMS. Repetitive transcranial magnetic stimulation dilakukan sebanyak 2000 pulse dengan frekuensi 10Hz. Nyeri diukur dengan Numerical Pain Rating Scale (NPRS) sebelum dan pascaterapi hingga hari ke-10. Analisis data dilakukan dengan uji Mann-Whitney.Hasil: Didapatkan 30 subjek yang dibagi menjadi 2 kelompok (15 kontrol dan 15 perlakuan). Selisih skor NPRS setelah sepuluh hari terapi lebih besar secara signifikan pada kelompok perlakuan dibandingkan dengan kontrol (6,67 vs 4,67, p=0,002).Diskusi: Terdapat penurunan intensitas nyeri yang signifikan pada kelompok yang diberikan r-TMS selama 10 siklus.Kata kunci: Central pain, NPRS, stroke, r-TMS